2008
DOI: 10.1016/j.psychres.2007.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Remitted depression moderates self-injurious behavior in personality-disordered research volunteers

Abstract: The moderating effects of depression on self-injurious behavior among personality-disordered individuals (N = 40) was examined. Self-injurious behavior (SIB) was assessed using a well-validated laboratory measure. Remitted depression was associated with greater sensitivity to self-aggressive cues, indicating that remitted depression may be a risk factor for SIB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…For each block, average self‐shock was computed. Validity for the inferences that can be drawn from an individual’s behavior during the SAP are supported by the positive associations between shock intensity and self‐ratings of self‐aggressive (i.e., NSSI and suicidal) disposition, along with other variables related to extra‐laboratory self‐injurious behaviors (Berman, Jones, & McCloskey, 2005; Berman & Walley, 2003; McCloskey & Berman, 2003; McCloskey, Gollan, & Berman, 2008).…”
mentioning
confidence: 96%
“…For each block, average self‐shock was computed. Validity for the inferences that can be drawn from an individual’s behavior during the SAP are supported by the positive associations between shock intensity and self‐ratings of self‐aggressive (i.e., NSSI and suicidal) disposition, along with other variables related to extra‐laboratory self‐injurious behaviors (Berman, Jones, & McCloskey, 2005; Berman & Walley, 2003; McCloskey & Berman, 2003; McCloskey, Gollan, & Berman, 2008).…”
mentioning
confidence: 96%
“…The entire task, including completing the pain threshold procedures, takes approximately 18 minutes to complete. As previous research has reported group differences on shock selection (see McCloskey, Ben-Zeev, Lee, Berman, & Coccaro, 2009;McCloskey, Gollan, & Berman, 2008;McCloskey, Look, Chen, Pajoumand, & Berman, 2012), this information will not be included in the current study.…”
Section: History Of Self-injuriousmentioning
confidence: 99%
“…External validity for the SAP is supported by the notion that the laboratory correlates of SAP behavior parallel those observed for extralaboratory ("real-world") self-injurious behaviors, including compromised 5-HT functioning (McCloskey et al, 2009), benzodiazepine consumption (Berman et al, 2005), alcohol intoxication (Berman, Bradley, et al, 2009;McCloskey & Berman, 2003), history of depression (McCloskey, Gollan, & Berman, 2008), and model effects (Berman & Walley, 2003;Sloan, Berman, Zeigler-Hill, & Bullock, 2009). In the absence of predisposing conditions (e.g., social influences, suicidal history, alcohol intoxication) the 20 shock is rarely selected.…”
Section: Measures the Deliberate Self-harm Inventory (Dshi; Gratz 2001)mentioning
confidence: 99%